An Australian incremental guideline for particulate matter (PM2.5) to assist in development and planning decisions - Adam Capon; Jackie Wright (Public Health Research & Practice, 2019)
Objectives: Many large-scale developments in Australia, such as road infrastructure, are subject to community concern due to their ongoing emission of particulate matter that may lead to adverse health impacts. The assessment of these impacts is guided by planning and health policies, but these policies have limitations. The objective of this paper is to provide an approach to setting an incremental guideline that can be used by regulators and health professionals to assess the impact of particulate matter from a development on a population, specifically the impact of particulate matter less than or equal to 2.5 micrometres in diameter (PM2.5).